Different Impacts on the Heart After COVID-19 Infection and Vaccination: Insights From Cardiovascular Magnetic Resonance - Gröschel, Jan; Bhoyroo, Yashraj; Blaszczyk, Edyta; Trauzeddel, Ralf Felix; Viezzer, Darian; Saad, Hadil; Fenski, Maximilian; Schulz-Menger, Jeanette (Frontiers in Cardiovascular Medicine, 2022)
Introduction Myocarditis-like findings after COVID-19 infection and vaccination were reported by applying Cardiovascular Magnetic Resonance (CMR). These results are very heterogenous and dependent on several factors like hospital admission or outpatient treatment, timing of CMR and symptomatic load. This retrospective study aimed to identify differences in myocardial damage in patients with persistent symptoms both after COVID-19 infection and vaccine by applying CMR. Methods This study entails a retrospective analysis of consecutive patients referred for CMR between August 2020 and November 2021 with persistent symptoms after COVID-19 infection or vaccination. Patients were compared to healthy controls (HC). All patients underwent a CMR exam in a 1.5 T scanner with a scan protocol including: cine imaging for biventricular function and strain assessment using feature tracking, T2-mapping for the quantification of edema, T1-mapping for diffuse fibrosis and late gadolinium enhancement (LGE) for the detection and quantification of focal fibrosis. Patients were divided into a subacute COVID-19 (sCov) group with symptoms lasting <12 weeks, Post-COVID-19 (pCov) group with symptoms >12 weeks and patients after COVID-19 Vaccination (CovVac). Results 162 patients were recruited of which 141 were included for analysis. The median age in years (interquartile range (IQR)) of the entire cohort was 45(37-56) which included 83 women and 58 men. Subgroups were as follows (total patients per subgroup, median age in years (IQR), main gender): 34 sCov, 43(37-52), 19 women; 63 pCov, 52(39-58), 43 women; 44 CovVac, 43(32-56), 23 men; 44 HC (41(28-52), 24 women). Biventricular function was preserved and revealed no differences between groups. No active inflammation was detected by T2-Mapping. Global T1 values were higher in pCov in comparison to HC (median (IQR) in ms: pCov 1002ms(981-1023) vs. HC 987ms(963-1009) (p=0.005)) with other parings revealing no differences. In 49/141(34.6%) of patients, focal fibrosis was detectable with the majority having a nonischemic pattern (43/141; 30.4%; patients) with the subgroups after infection having more often a subepicardial pattern compared to CovVac (Total (% of group): sCov: 7/34(21%); pCov 13/63(21%); CovVac 2/44(5%) (p=0.04)). Conclusion Patients after COVID-19 infection showed more focal fibrosis in comparison to patients after COVID-19 vaccination without alterations in biventricular function.